2011
DOI: 10.1152/ajpregu.00562.2010
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the modulation of vasomotor sympathetic outflow during static handgrip exercise in healthy young humans

Abstract: Sex differences in sympathetic neural control during static exercise in humans are few and the findings are inconsistent. We hypothesized women would have an attenuated vasomotor sympathetic response to static exercise, which would be further reduced during the high sex hormone [midluteal (ML)] vs. the low hormone phase [early follicular (EF)]. We measured heart rate (HR), blood pressure (BP), and muscle sympathetic nerve activity (MSNA) in 11 women and 10 men during a cold pressor test (CPT) and static handgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
152
4
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(175 citation statements)
references
References 39 publications
13
152
4
1
Order By: Relevance
“…In contrast, during CPT, MSNA responses were not different during differing hormonal phases (10). Jarvis and colleagues (20) examined sympathetic responses to static handgrip exercise and during CPT in non-OCP users during EF and ML phases and in age-matched men. Sympathetic responses during static exercise and posthandgrip circulatory arrest were greater in men than in either hormonal phase in women, which were not different from each other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, during CPT, MSNA responses were not different during differing hormonal phases (10). Jarvis and colleagues (20) examined sympathetic responses to static handgrip exercise and during CPT in non-OCP users during EF and ML phases and in age-matched men. Sympathetic responses during static exercise and posthandgrip circulatory arrest were greater in men than in either hormonal phase in women, which were not different from each other.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitantly, basal sympathetic nerve activity (SNA) has been shown to follow a cyclical pattern with the ovarian cycle in premenopausal women. Some (27, 31), but not all (3,4,10,12,20,22,23), investigators have previously reported that resting SNA directed to the vascular bed of muscle displays a cyclical pattern in healthy nonsmoking, premenopausal females. Resting muscle sympathetic nerve activity (MSNA) is increased during the ML, high-hormone, phase following ovulation and is decreased during the EF, low-hormone phase during menses.…”
mentioning
confidence: 99%
“…These results support a change in central integration of the carotid chemoreceptor feedback with metaboreflex activation and help explain previous evidence of carotid chemoreceptor activation during exercise despite no increase in circulating carotid chemoreceptor stimuli. Our investigation was only done in young healthy men; however, it would be of interest to investigate the interactions between the metaboreflex and the chemoreflex in young women, particularly considering that the metaboreflex is less sensitive in women (18). It would also be prudent to investigate these interactions in clinical populations such as chronic heart failure as it has been shown to enhance both the metaboreflex (14,24) and chemoreflex (33,36).…”
Section: Perspectives and Significancementioning
confidence: 99%
“…In young women, there have been mixed results as to whether the fluctuations in ovarian hormones alter baroreflex control of sympathetic activity. Minson et al (29) reported an increase in MSNA sensitivity in the mid-luteal phase compared with the early follicular phase using the Modified Oxford method, whereas others have reported no changes across the same menstrual phases using a variety of techniques (6,14,22,27). Similarly, combined oral contraceptives have been shown to either decrease (30) or have no effect on (5, 27) sympathetic baroreflex sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies have found no differences in both cardiovagal (8,17,29) and sympathetic (6,14,22) baroreflex sensitivity between the early follicular (low hormone) and mid-luteal (high estrogen and progesterone) phases, but this is not true of all studies (20,42,44). It is possible that estrogen and progesterone have opposing influences on the baroreflex, necessitating study of the individual actions of the hormones.…”
mentioning
confidence: 99%